ANALISIS PENGGUNAAN ANTIBIOTIKA YANG TIDAK RASIONAL PADA BALITA PENDERITA BUKAN PENUMONIA DI KOTA PADANG - Siswati, Sri (Lembaga Penelitian Universitas Negeri Padang, 2009)
Irrational drug use such as antibiotic for non pneumonic acute respiratory tract infections is the problems, because reduction in the quality of drug therapy leading to increased morbidity and mortality, increased cost, adverse reactions and bacterial resistance. Antibiotic use for non pneumonic acute respiratory tract infections and non specific diarrhea in Center Health Padang City, average 28,%. It is much higher than ideal target of 0% and still hight than province target of less than 20%. The aim of this study to know how much antibiotic proportion use in children under five years with non pneumonic acute respiratory tract infections, and to know about relationship independent variabel such as backgrouns study, knowledge, attitude of standart treatment, skill of dicision diagnosis, patiens demands, supervisition and formal training with dependent variable antibiotic use for children under five years with non pneumonic acute respiratory tract infections. Study with Quantitatif method with cross sectional desain . Result of antibiotic use proportions 24,3%, and relationship analysis in quantitative method result significant relationship between knowledge, attitude of standart treatment, supervision, and formal training with antibiotic use for children under five years with non pneumonic acute respiratory tract infections. Result study may use to decrease irrational antibiotic to many desease, specially to decision making for antibiotic interventions use for non pneumonic acute respiratory tract infections. Key Words: Antibiotic, ISPA non-pneumonia, Irrational drug use.